Hubungan antara Kualitas Tidur dengan Tingkat Stres pada Mahasiswa Fakultas Kedokteran Universitas Mulawarman: Relationship Between Sleep Quality and Stress Level in Student of Medical Faculty of Mulawarman University - Muh. Rijal Muttaqin; Denny Jeffry Rotinsulu; Sulistiawati Sulistiawati (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Sleep is an important biological process for optimal life and health. Good quality of sleep will make the body feel refreshed and fit again when waking from sleep. Sleep quality which is an important factor for health consists of quantitative components, such as sleep duration, as well as qualitative components such as sleep latency, sleep disturbances, and daytime dysfunction. Poor sleep quality can interfere with the neuroendocrine function of the stress response, leading to the occurrence of stress-related disorders such as depression and mood disorders. This study, which uses observational analytical methods with a cross-sectional approach, aims to determine the relationship between sleep quality and stress levels in students of the Faculty of Medicine, Mulawarman University. Sleep quality measured by Pittsburgh’s Sleep Quality Index questionnaire and stress level measured by Perceived Stress Scale questionnaire with the help of google form. The research sample consisted of students of the Faculty of Medicine of Mulawarman University which amounted to 353 students from the class of 2017, 2018, 2019 and 2020 Medical Studies Program. The results showed that more students of Mulawarman University Faculty of Medicine had poor sleep quality (75.9%), and experienced moderate stress levels (75.1%). Moderate stress levels were most experienced by respondents who had poor sleep quality (60.9%) with a value relationship of p= 0.000. It can be concluded that there is a significant relationship between sleep quality and stress levels in students of the Faculty of Medicine, Mulawarman University.